From oncology hospital to covid free oncology hospital - Branco, Paula (2020)
In early 2020, Portugal faced the SARS-CoV-2 pandemic. The Lisbon’s Portuguese Institute of Oncology Francisco Gentil, prepared itself to assure the screening and due treatment of cancer patients with COVID-19. A contingency plan was drawn up, a crisis task force was appointed and a containment area was created. In April 2020 the Ministry of Health declared the Portuguese Institutes of Oncology as hospitals isolated from those that would treat COVID-19 patients. The crisis task force maintained the internal management of the pandemic, as well as the liaising with the Hospitals that treated COVID-19patients. In this article, we will discuss how this Institution, being a hospital not directed to the treatment of COVID-19 patients, dealt with this pandemic.